Mutual Acculturation of Russians and Armenians in the Krasnodar Territory - Victoria N. Galyapina; Oksana R. Tuchina; Ivan A. Apollonov (Peoples' Friendship University of Russia (RUDN University), 2023)
Mutual intercultural relations between the dominant population and representatives of ethnic minorities or migrants have been studied in sufficient detail by both foreign and Russian researchers. However, some minorities have a special status and are referred to by Russian researchers as 'indigenized' ones. Armenians belong to such ethnic groups. In this regard, it is of interest to study the mutual intercultural relations between representatives of the ethnic majority and Armenians as an indigenized ethnic minority. This study was conducted in the context of J. Berry's ecocultural approach. The purpose of the study was to test three hypotheses of intercultural relations (multiculturalism, contact and integration). The sample included Russians ( N = 198; men - 50%; M age = 19.7) and Armenians ( N = 186, men - 43%, M age = 23.3) from the Krasnodar territory, the total sample N = 388. The research methods included scales from the MIRIPS questionnaire adapted to the Russian sample. Using structural equation modeling, the results indicating that the perceived security of the Russian and Armenian respondents predicted their attitudes to support a multicultural ideology were obtained; for the Armenians, this was also positively associated with the integration strategy and negatively associated with the assimilation attitudes. Intercultural friendly contacts among Russians and Armenians were positively associated with ethnic tolerance; however, among the Armenians they were also associated with the integration and assimilation strategies. The Armenians' preference for the separation strategy predicted their life satisfaction; for the Russians, however, their expectation of the Armenians' separation did not contribute to their self-esteem. In general, the results of the study had shown that the perceived security and especially intensive intercultural friendly contacts lead to the mutual integration of the non-indigenous ethnic minority and the ethnic majority. The historically determined features of the Krasnodar territory, multiculturalism and multiconfessionalism, as well as the absence of assimilation imposed by the ethnic majority, are important conditions for the successful mutual acculturation of the Russians and representatives of the 'indigenized ethnic minority', i.e., the Armenians of the Kuban.